Quantitative Measurement of Redox State in Human Brain by (31)P MRS at 7T with Spectral Simplification and Inclusion of Multiple Nucleotide Sugar Components in Data Analysis - Ren, Jimin (Magn Reson Med, 2020)
PURPOSE: To develop a simplified method for quantitative measurement of NAD(+)/NADH levels in human brain by (31)P MRS without interference from the α-ATP signal and with inclusion of multiple UDP-sugar components. METHODS: Simple pulse-acquire (31)P MR spectra were collected at 7T with and without a frequency-selective inversion pulse to remove the dominant α-ATP signal from the underlying NAD(H) signal. Careful inspection of the (31)P signal at −9.8 ppm previously assigned to UDP-glucose revealed multiple UDP-sugar components that must also be considered when deconvoluting the NAD(H) signal to quantify NAD(+) and NADH. Finally, the overlapping NAD(H) and UDP(G) resonances were deconvoluted into individual components using Voigt lineshape analysis and UDP(G) modeling. RESULTS: The frequency-selective inversion/subtraction method enabled clean separation of the NAD(H) signal from the otherwise dominant α-ATP signal. In addition, the upfield signal near −9.8 ppm appears more “quartet-like” than a simple doublet consistent with contributions from other nucleotide sugars such as UDP-galactose, UDP-N-acetyl-galactosamine, and UDP-N-acetyl-glucosamine in addition to UDP-glucose. Deconvolution of the combined NAD(H) and UDP(G) signals showed that the measured NAD(+)/NAD ratio was heavily influenced by UDP(G) modeling (7.5±1.8 when the UDP(G) signal was fitted as multiple doublets versus 5.3±0.6 when a simplified pseudo doublet model was used). In a test/re-test experiments separated by two weeks, consistent NAD(+)/NADH ratios were measured in the brain of seven human subjects. CONCLUSIONS: The NAD(+)/NADH ratio in human brain can be measured using (31)P MR spectra simplified by spectral editing and with inclusion of multiple UDP-sugar components in the data analysis.